THE CONCEPTOSPHERE OF SILENCE IN ARTISTIC PRACTICES OF JAPAN - Рибалко, С. Б. (Art and Design, 2023)
Purpose: to highlight philosophical and religious basis of the concept of silence and its derivatives, which together form a single semantic field, to determine its functions and representations in various areas of artistic practice. Methodology. An integrated approach to the study of the conceptosphere of silence was used, which made it possible to determine its components and manifestations in a variety of traditional and modern artistic practices in Japan. In the process of research, methods and techniques of formal, figurative-stylistic, semiotic, comparative and content analysis were used. The work is based on the research work of various branches of the humanities; results of field research were carried out in 2005–2019. Results. The main factors of formation and components of the conceptosphere of silence in Japanese culture are considered. The main forms and means of representing silence are highlighted on the example of works of fine art, visual and performative practices: sculpture, painting, graphics, ikebana, tea ceremony, traditional and modern forms of dance and theater, cinematography. Scientific novelty. The means of visualizing the concept of silence in Japanese art, subject-thematic complexes associated with it and leading approaches are determined. It has been established that the concept of silence is realized in audial and visual dimensions and is one of the fundamental cores of Japanese art. Practical significance. The considered principles of using silence as artistically expressed means can be applied in the development of a methodology for the analysis of works of Japanese art and subsequent studies of its morphology. The results of the work can be creatively interpreted in visual and performative practices and used in the development of exhibition projects.